THERE IS, PROBABLY, NO NEED FOR A DESIGN FRAMEWORK - de Lange, Jan (Journal on Mathematics Education, 2021)
I present my perspective on the design process in this article, arguing for a focus on student learning and "slow design" that stems from knowledge of mathematics and their support system in the learning process. I have a question about the design process academization and task design research direction. Numerous examples from my work at the Freudenthal Institute are used to illustrate this paper.